WS2/MoS2 Heterostructures through Thermal Treatment of MoS2 Layers Electrostatically Functionalized with W3S4 Molecular Clusters. Issue 29 (30th March 2020) - Morant‐Giner, Marc; Brotons‐Alcázar, Isaac; Shmelev, Nikita Y.; Gushchin, Artem L.; Norman, Luke T.; Khlobystov, Andrei N.; Alberola, Antonio; Tatay, Sergio; Canet‐Ferrer, Josep; Forment‐Aliaga, Alicia; Coronado, Eugenio
Abstract: The preparation of 2D stacked layers combining flakes of different nature gives rise to countless numbers of heterostructures where new band alignments, defined at the interfaces, control the electronic properties of the system. Among the large family of 2D/2D heterostructures, the one formed by the combination of the most common semiconducting transition metal dichalcogenides, WS2 /MoS2, has awakened great interest owing to its photovoltaic and photoelectrochemical properties. Solution as well as dry physical methods have been developed to optimize the synthesis of these heterostructures. Here, a suspension of negatively charged MoS2 flakes is mixed with a methanolic solution of a cationic W3 S4 ‐core cluster, giving rise to a homogeneous distribution of the clusters over the layers. In a second step, a calcination of this molecular/2D heterostructure under N2 leads to the formation of clean WS2 /MoS2 heterostructures, where the photoluminescence of both counterparts is quenched, proving an efficient interlayer coupling. Thus, this chemical method combines the advantages of a solution approach (simple, scalable, and low‐cost) with the good quality interfaces reached by using more complicated traditional physical methods. Abstract : Stacked layers : The reported simple and scalable chemical strategy for the preparation of WS2 /MoS2 stacked layers gives rise to clean heterostructures with strong interlayer interaction. MoS2 flakes with a negatively charged surface are functionalized with a cationic W cluster, which undergoes a dry thermal decomposition into thin WS2 layers. The quenching of the photoluminescence signal in the prepared heterostructure proves an efficient interlayer coupling.